Qualidade de vida no esporte como trabalho de atletas paralímpicos brasileiros - Cortes, Nancy Edith Pinilla (2021)
Changes in the world of work impact the workers’ performance in their work contexts, quality of life, health levels, family, and social life. It is in this context of continuous transformation that are the Paralympic athletes, here considered as workers. Thus, from the sport-work binomial, sport is a professional exercise. The present study aims to comprehend what is quality of life in the sport-work of Brazilian Paralympic athletes of the track and field modality, who are in preparation for the next edition of the Paralympic Games, and what are the main factors that result in experiences of wellbeing and malaise in that work context. This is an exploratory-descriptive research, with a qualitative approach. For data collection, we conducted online in-depth interviews and with a semi-structured script, developed with open-ended questions on the athletes’ life history, characterization of sport-work and related to the factors that constitute the Activity-Centered Ergonomics applied to Quality of Life at Work. We interviewed 11 parathletes, already classified or close to obtaining the index for the Paralympic Games’ participation. We opted for the content thematic analysis with the support of the software Novo NVivo. We identified 4 categories: 1) An overcoming journey: the place of disability and sport in the Paralympic athlete’s life; 2) Sport as work: an unveiled relationship; 3) Quality of life constituent factors in sport as work from the perspective of parathletes; and 4) COVID-19 pandemic impact and Tokyo Paralympic Games postponement. The categories allowed to retrieve evidence from the parathlete perspective about their conception on the sport as work. The achievements and fulfillment achieved through sport brought a new meaning to their condition of disability, allowing a professional identification, pointing out that the work activity carry out a social purpose.